1982
DOI: 10.1111/j.1439-0418.1982.tb03564.x
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachtin: A potent insect growth regulator of plant origin

Abstract: Azadirachtin, a potent antifeedant and growth regulator from the neem tree, Azadirachta indica A. Juss, was tested against three holometabolous insects belonging to different orders: Mexican bean beetle, Epilachna varivestis Muls.; Mediterranean flour moth, Ephestia kuehniella Zell.; and honeybee, Apis mellifera L. Different amounts of azadirachtin were either fed (E. varivestis, fourth instar larvae) or topically applied (E. kuehniella, last larval instar, spinning stage; A. mellifera, third instar larvae) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The efficacy of neem products may vary with respect to concentrations of azadirachtin [38], and thus some authors have stated lower insecticidal activity against CPB [39,40]. However, that was not the case in our study, because the commercial product NeemAzal T/S (Trifolio-M GmbH, Lahnau, Germany) used in the bioassay contains 1% of the purified active ingredient Azadirachtin A, which is a very potent insect growth inhibitor [41] (reviewed in [19,42]). In the case of karanja oil, higher doses were needed to achieve the same mortality of CPB larvae as with neem oil.…”
Section: Discussionmentioning
confidence: 66%
“…The efficacy of neem products may vary with respect to concentrations of azadirachtin [38], and thus some authors have stated lower insecticidal activity against CPB [39,40]. However, that was not the case in our study, because the commercial product NeemAzal T/S (Trifolio-M GmbH, Lahnau, Germany) used in the bioassay contains 1% of the purified active ingredient Azadirachtin A, which is a very potent insect growth inhibitor [41] (reviewed in [19,42]). In the case of karanja oil, higher doses were needed to achieve the same mortality of CPB larvae as with neem oil.…”
Section: Discussionmentioning
confidence: 66%
“…Similar results have also been observed when larvae of S. littoralis are treated with extracts of Commiphora molmol (Shonouda et al 2000) or S. frugiperda larvae are treated with Calceolaria talcana extracts (Munoz et al 2013). It appears that the plant extracts are mimicking the action of JH which suppresses pupation (Eto 1990) and may also block the synthesis/release of eclosion hormone since phytochemicals are known to suppress the synthesis of ecdysteroids or eclosion hormone (Rembold et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In insects, it was observed that even the lower concentrations of azadirachtin interfered with the animal physiology with the largest effect being fully inhibiting the feeding process, thereby allowing control of them (Warthen 1989). It inhibits feeding and growth of insects belonging to several orders like Lepidoptera (Koul et al 1987), Diptera (Champagne et al 1989), Orthoptera (Rao and Subrahmanyam 1986;Ascher et al 1989), Hemiptera (Dorn 1986;Dorn et al 1986), Coleoptera (Meisner and Mitchell 1982;Ladd et al 1984), Hymenoptera (Rembold et al 1982), etc. through intervention in endocrine events (Sieber and Rembold 1983; and Blackwell 1993; Malczewska et al 1988;Subrahmanyam et al 1989;Barnby and Klocke 1990).…”
Section: Introductionmentioning
confidence: 99%